Determination of the effect of the open cell foam material geometry on the value of energy efficiency - O. V. Soloveva; S. A. Solovev; Yu. V. Vankov; I. G. Akhmetova; R. Z. Shakurova; A. R. Talipova (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Improving the energy efficiency of open cell foam materials with different geometries (SC, BCC, FCC, DEM) and with different medium porosities (ε=0.7; ε=0.75; ε=0.8; ε=0.85; ε=0.9; ε=0.95) by numerical simulation. To determine the influence of the geometry and porosity of an open cell foam material on the values of pressure drop, heat flux and energy efficiency factor.METHODS .Numerical simulation was carried out using the ANSYS Fluent 19.2 software package. Geometric models of porous structures are sets of intersecting spheres with different packing structures: periodic Simple Cubic packing (SC), Face Centered Cubic packing (FCC), Body Centered Cubic packing (BCC), and random structure generated by the discrete element method (DEM).The calculations were carried out at the following air flow velocities: 0.01; 0.05; 0.25; 0.5; 0.75; 1; 1.25 m/s.RESULTS. Atair flow velocities of 0.01 m/s and 0.05 m/s, all the studied structures show approximately the same heat flux. With porosity values ε=0.75; ε=0.8; ε=0.85 the highest values of heat flow were shown by the FCC structure, with porosity ε=0.7; ε=0.9; ε=0.95 the BCC structure had the highest heat flux. This is explained by the fact that, at the corresponding porosity values, the FCC or BCC structure had the largest surface area, which provided the largest heat flux. With the porosities of media ε=0.7 and ε=0.75, the BCC and FCC cell packages show a high pressure drop. With the porosities of media ε=0.8 and ε=0.85, the highest pressure drop corresponds to FCC cell packing, and for porosities ε=0.9 and ε=0.95, to BCC cell packing.CONCLUSION. With equal high porosity, the BCC cell packing provides a higher value of heat flux than the FCC structure. The SC package has the lowest heat flux values for all studied porosities. The SC package also has the lowest pressure drop values and therefore the highest energy efficiency values.